Studies in Grassland Ecology of the Maharashtra State I. Ecological Classification of Grassland Patterns Found in Different Ecological Habitats and their Botanical Characterization - Oke, J. G. (Indian Forester, 1972)
Ecological classification of grasslands in Maharashtra state into seven major habitat patterns and twentyfour minor sub-patterns has been attempted on the basis of soil, topography, hydrography and otber phenological considerations. Each of these major patterns and subpatterns have beeen subjected to critical botanical characterization and their respective botanical associations of typical herbs and shrubs as index species along with their component grass species in the order of their dominance. This provides a better defnition for the local grassland patterns.